Postvaccination COVID‐19 infection is associated with reduced mortality in patients with cirrhosis. Issue 1 (22nd February 2022) - John, Binu V.; Deng, Yangyang; Schwartz, Kaley B.; Taddei, Tamar H.; Kaplan, David E.; Martin, Paul; Chao, Hann‐Hsiang; Dahman, Bassam
Abstract: Background and Aims: Patients develop breakthrough COVID‐19 infection despite vaccination. The aim of this study was to identify outcomes in patients with cirrhosis who developed postvaccination COVID‐19. Methods: We performed a retrospective cohort study among US veterans with cirrhosis and postvaccination or unvaccinated COVID‐19. Patients were considered fully vaccinated if COVID‐19 was diagnosed 14 days after the second dose of either the Pfizer BNT162b2, the Moderna 1273‐mRNA, or the single‐dose Janssen Ad.26.COV2.S vaccines and partially vaccinated if COVID‐19 was diagnosed 7 days after the first dose of any vaccine but prior to full vaccination. We investigated the association of postvaccination COVID‐19 with mortality. Results: We identified 3242 unvaccinated and 254 postvaccination COVID‐19 patients with cirrhosis (82 after full and 172 after partial vaccination). In a multivariable analysis of a 1:2 propensity‐matched cohort including vaccinated ( n = 254) and unvaccinated ( n = 508) participants, postvaccination COVID‐19 was associated with reduced risk of death (adjusted HR [aHR], 0.21; 95% CI, 0.11–0.42). The reduction was observed after both full (aHR, 0.22; 95% CI, 0.08–0.63) and partial (aHR, 0.19; 95% CI, 0.07–0.54) vaccination, following the 1273‐mRNA (aHR, 0.12; 95% CI 0.04–0.37) and BNT162b2 (aHR, 0.27; 95% CI, 0.10–0.71) vaccines and among patients with compensated (aHR, 0.19; 95% CI, 0.08–0.45) and decompensated (aHR, 0.27; 95% CI, 0.08–0.90) cirrhosis. Findings were consistent in a sensitivity analysis restricted to participants who developed COVID‐19 after vaccine availability. Conclusions: Though patients with cirrhosis can develop breakthrough COVID‐19 after full or partial vaccination, these infections are associated with reduced mortality. Abstract : image